Investment banking : valuation, leveraged buyouts, and mergers & acquisitions - Rosenbaum, Joshua, 1971- (Wiley finance series., 2009)
In the constantly evolving world of finance, a solid technical foundation is an essential tool for success. Due to the fast-paced nature of this world, however, no one has been able to take the time to properly codify the lifeblood of the corporate financier's work--namely, valuation. Rosenbaum and Pearl have responded to this need by writing the book that they wish had existed when they were trying to break into Wall Street. Investment Banking: Valuation, Leveraged Buyouts, and Mergers & Acquisitions is a highly accessible and authoritative book that focuses on the primary valuation methodolog.